MEDIA IN INCREASING STUDENTS’ VOCABULARIES REGARDING COVID-19 TERMS - Nurjanah Hadianti, Siti (Lembaga P3M, 2020)
This research aimed to find out the influence of media in increasing students’ vocabularies regarding COVID- 19 terms and which media comes dominantly. It is employed by qualitative-descriptive method with percentage result. The data was taken from online news which limited about terms regarding COVID-19. Students in second semester with non-English background study was asked to fill in questionnaire. After collecting the data, the result shows that almost all responders know the terms regarding COVID-19 in more than 50% in each of terms, while only one term found with less percentage than that. In other hand, media which comes as a majority is Internet or online media with the highest percentage than another media in all terms. So, it can be concluded that online media or internet influences the student’s vocabularies regarding COVID-19.